Melting of multipass surface tracks in steel incorporating titanium carbide powders - Mridha, Shahjahan; Md Idriss, Ahmed Nazrin; Maleque, Md. Abdul; Yaacob, Iskandar Idris; Baker, T. Neville (Maney Online, 2015)
Overlapping tracks were processed by melting preplaced titanium carbide (TiC) powder on steel surfaces using a tungsten inert gas torch. The tracks produced y1?0 mm melt depth free from cracks, but occasional pores were observed. The microstructure consisted of unmelted and partially melted TiC particulates together with reprecipitated TiC particles, which were prominent in tracks processed in the initial stage. A greater number of reprecipitated globular and cubic TiC particles were observed in tracks processed in the later stages, indicating more dissolution of TiC particulates from the overlapping operation. Those multitracks processed in the initial stage developed a maximum hardness of 850–1000 HV, which was lower in most other tracks, although comparable hardness values were recorded in the last track.